The critique of Gĩkũyũ religion and culture in S.N. Ngũbiah's A curse from God - Hale, F. (Faculty of Theology, University of the Free State, 2007)
The relationship between missionary Christianity and traditional African cultures was a prominent theme in post-colonial literature during and for many years after the era of decolonisation.In contrast to the nostalgic defensiveness of many Kenyan and other post-colonial African writers, perhaps most notably Ngugi wa Thiong’o, the Gikuyu novelist S.N. Ngubiah found not salvation but a burden in certain aspects of his precolonialist indigenous culture. In his novel A curse from God (1970) Ngubiah challenges obliquely but unmistakably the long-accepted position of his fellow Gikuyu (and first national leader of independent Kenya) Jomo Kenyatta, particularly as argued in Facing Mount Kenya , that a return to tribal folkways was a precondition to economic and social upliftment.This clash between a traditionalist and a modernist exemplifies the larger predicament facing African societies as they undergo rapid religio-cultural transformation. At least as early as the 1950s, and seen perhaps most vividly in Chinua Achebe’s Things fall apart , African littérateurs began to use fiction as a forum in which to challenge the tribulations resulting from the impact of European cultures on their own.In general terms, this soon became a recurrent theme in postcolonial African literature in English, French, and other languages. A minor counter-current developed, however, when some African writers began to emphasise their conviction that at least part of the genesis of the woes they saw around them came from within and criticised the facile use of foreign cultural intrusions as scapegoats, particularly when that practice distracted from what they regarded as a need for internal reform.In the present article I shall examine how one such writer, Kenyan novelist S.N. Ngubiah, crossed verbal swords with the internationally renowned champion of Gikuyu culture and first post-independence leader of Kenya, Jomo Kenyatta, in his novel of 1970, A curse from God .
Keywords: Gĩkũyũ religion; S.N. Ngũbiah; A curse from God